Spectral analysis of vibrations in control investigations of vibroacoustic heads KGS-320 - ZAKRZEWSKI, Tadeusz (Archives of Acoustics, 1987)
Diagnostic investigations were performed in order to evaluate the usability of the spectral analysis of vibrations in the process of control diagnostics of vibroacoustic arm heads of combined cutter loaders KGS 320. Tests were carried out at the acceptance inspection stand during idle running of the head with the consideration of both directions of rotation of the output shaft.Frequency components corresponding to rotational speeds of some kinematic elements of the system under investigation were isolated on the basis of the spectral analysis of vibrations. A comparison of discrete amplitudes obtained from vibration spectra, allowed to evaluate the range of variability of vibration levels in determined frequency bands, as well as to isolate some kinematic pairs, which are characterised by the maximal vibration intensity. It was found that the rotation direction of the output shaft influences values of amplitudes of some vibration parameters in frequency bands, which contain characteristic frequencies of some elements of the system.